Determinan Kualitas Audit (Studi Kasus pada Kantor Akuntan Publik di Kota Semarang) - Nugroho, Tito Garin; Sinarasri, Andwiani; Kristiana, Ida (Jurnal Ilmiah Aset, 2024)
This study aims to examine the effect of independence, accountability, audit complexity and auditors work experience on audit quality. This study uses a quantitative approach. The population in this study is a Public Accounting Firm in Semarang City. The sample of this research is 65 respondents. Data analysis used multiple linear regression and hypothesis testing using SPSS 25 program. The results showed that the independence variable and auditors work experience had no effect on audit quality, accountability and audit complexity variables had a positive effect on audit quality. Meanwhile, the variables of independence, accountability, audit complexity and auditors work experience simultaneously affect audit quality